Integrated flow cytometry data quality control - SPEDRON, JOSEPH; PASTAKIA, MITJA; GOLDEN MICHAEL; PREISSLER THOMAS; PURCELL PAUL BARKLEY; OSBORNE GEOFFREY (2023)
Aspects of the present disclosure include methods for integrating data quality assessment with data acquisition of a flow cytometer. A method according to certain embodiments includes detecting light from a sample illuminated by a light source in a flow stream with a light detection system, generating an event data signal in response to an event detected with the light detection system, binning the generated event data signal in a plurality of binning windows having overlapping data bins, and evaluating a plurality of binning windows for outlier events in the generated data signal. A system having a processor having memory with instructions for practicing the subject methods is also described. A non-transitory computer-readable storage medium is also provided. 本公开的各方面包括用于将数据质量评估与流式细胞仪的数据采集集成的方法。根据某些实施例的方法包括用光探测系统探测来自流动流中的被光源照射的样品的光，响应于用光探测系统探测的事件生成事件数据信号，将生成的事件数据信号分仓在具有重叠数据仓的多个分仓窗口中，以及针对生成的数据信号中的离群值事件评估多个分仓窗口。还描述了具有处理器的系统，该处理器具有存储器，该存储器具有用于实践主题方法的指令。还提供非暂时性计算机可读存储介质。